Chronic Hepatitis C Virus Infection Impairs M1 Macrophage Differentiation and Contributes to CD8+ T-Cell Dysfunction - Faria Ahmed; Andrea Ibrahim; Curtis L. Cooper; Ashok Kumar; Angela M. Crawley (Cells, 2019)
Chronic hepatitis C virus (HCV) infection causes generalized CD8+ T cell impairment, not limited to HCV-specific CD8+ T-cells. Liver-infiltrating monocyte-derived macrophages (MDMs) contribute to the local micro-environment and can interact with and influence cells routinely trafficking through the liver, including CD8+ T-cells. MDMs can be polarized into M1 (classically activated) and M2a, M2b, and M2c (alternatively activated) phenotypes that perform pro- and anti-inflammatory functions, respectively. The impact of chronic HCV infection on MDM subset functions is not known. Our results show that M1 cells generated from chronic HCV patients acquire M2 characteristics, such as increased CD86 expression and IL-10 secretion, compared to uninfected controls. In contrast, M2 subsets from HCV-infected individuals acquired M1-like features by secreting more IL-12 and IFN-γ. The severity of liver disease was also associated with altered macrophage subset differentiation. In co-cultures with autologous CD8+ T-cells from controls, M1 macrophages alone significantly increased CD8+ T cell IFN-γ expression in a cytokine-independent and cell-contact-dependent manner. However, M1 macrophages from HCV-infected individuals significantly decreased IFN-γ expression in CD8+ T-cells. Therefore, altered M1 macrophage differentiation in chronic HCV infection may contribute to observed CD8+ T-cell dysfunction. Understanding the immunological perturbations in chronic HCV infection will lead to the identification of therapeutic targets to restore immune function in HCV+ individuals, and aid in the mitigation of associated negative clinical outcomes.